A comparison study of removal of methylene blue dye by adsorption on Neem leaf powder (NLP) and activated NLP - Patel, Himanshu; Vashi, R. T. (Journal of Environmental Engineering and Landscape Management, 2013)
The adsorption of basic dye, Methylene Blue Dye (MBD) onto neem (Azadirachta indica) leaf powder (NLP) and activated NLP with sulphuric acid was compared in this investigation. The surface analyses of NLP and activated NLP (particle size distribution, porosity, pore volume, pore diameter and BET surface area) were conducted using sophisticated instrument. The process parameters like adsorbent dose, pH, temperature and contact duration have been studied. The experimental data were analyzed using Langmuir and Freundlich isotherm, in which adsorption capacities and intensities were evaluated. Three kinetic models, pseudo first-, second-order and Elovic equations were applied to describe the adsorption process, in which correlation coefficient for each kinetic equation were calculated and evaluated.First published online: 11 Oct 2012